Dialog antarteks Toenggoel dan Ronggeng Dukuh Paruk: Melawan atau mengukuhkan tradisi - Sungkowati, Yulitin (citeus, 2010)
This paper examines the intertextuality between two novels, Toenggoel by Eer Asura and Ronggeng Dukuh Paruk (RDP) by Ahmad Tohari. The intertextual relations can be said to be strengthening. Toenggoel clarifies the idea in RDP, in that a person who tries to reject a tradition is destined to possess a tragic fate: eliminated and isolated from his society. Sapto Linggo in Toenggoel is eliminated from his so- ciety because he rejects the gemblak tradition, whereas Srintil, in RDP, goes crazy because she is not willing to submissively receive the ronggeng tradition.